The failure criterion based on hydrogen distribution ahead of the fatigue crack tip - Yu. G. Matvienko (Fracture and Structural Integrity)
The hydrogen effect on the fracture toughness and fatigue crack growth behaviour in the martensitic high strength steel is investigated. The secondary ion mass spectrometry method has been employed to analyse the distribution of hydrogen concentration in the zone of the crack tip and at its edges. Changes in hydrogen concentration are observed in the vicinity of the propagating crack tip and at a remote site. The hydrogen peak H C is reduced and moves away from the fatigue crack tip with the increase of the maximum stress intensity factor max K . The concept of damage evolution is used to explain fatigue crack propagation in connection with the hydrogen redistribution ahead of the crack tip. The physical failure criterion based on the hydrogen peak in the vicinity of the fatigue crack tip and the maximum stress intensity factor has been proposed. The criterion reflects changes in the hydrogen peak which resulted from the hydrogen redistribution due to the increase of the maximum stress intensity factor as the crack length increases under fatigue loading.